Edukasi pada Masyarakat Baduy-Banten dalam Upaya Pencegahan Covid-19 di Seluruh Lapisan Bumi (SEBUMI) - Desmawati Desmawati; Agustina Agustina; Dora Samaria; Ritanti Ritanti; Lina Ayu Marcelina (Jurnal Abdimas Kesehatan (JAK), 2022)
The community service activity "Everyone and Everywhere Prevents COVID-19" was carried out on Saturday-Sunday 28-29 May 2022, which was attended by 30 Baduy Lewi Damar communities, Serang Banten. The activity was carried out through several stages, namely: opening, pretest implementation before health counseling, counseling and presentation of health materials on Covid-19, discussion and question and answer sessions, posttest implementation, distribution of leaflets, and closing. This service activity has succeeded in providing understanding to the Baduy community, especially the Lewi Damar area, Serang, Banten regarding Covid-19, the importance of preventing Covid-19, and implementing health in the new normal era of the Covid-19 pandemic. The results of distributing the questionnaires showed that the increase in knowledge after education regarding the prevention of Covid-19 in the Baduy Lewi Damar community, Serang Banten.